Penyebab Ketidaklengkapan Data Diagnosis Pada Rekam Medis Elektronik Terkait Pelaporan(Rl5.3) di Rs St. Elisabeth Medan - Munthe, Josua Saputra; Suryati, Oktaviani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Electronic Medical Record (RME) is a computerized health information system that contains social data and patient medical data, and can be equipped with a decision support system. Electronic Medical Records can help better management of patient health services (Andriani et al., 2017). Santa Elisabeth Hospital Medan in inputting its Electronic Medical Record data already uses a web-based application. Where this web-based application is called Sphaira Mobile Electronic Medical Record. This application is still newly implemented and used in the electronic medical record system at the Santa Elisabeth Hospital Medan. With the transfer from manual medical records to electronic medical records, this has resulted in several problems in filling out patient electronic medical records. The purpose of this study was to determine the cause of the incomplete diagnosis data in electronic medical records related to the reporting of the top 10 inpatients (Rl5.3) at the Santa Elisabeth Hospital, Medan. The type of research used is descriptive and qualitative with observation and interview data collection techniques. Based on the results of interviews with the head of the medical record room at Santa Elisabeth Hospital Medan, he stated that the transition from manual medical records to electronic medical records made hospital employees, especially officers in the medical record room, have to adapt, recognize and learn how to operate the Sphaira Mobile Electronic Medical Record application. Factors Causes of incomplete diagnosis data in electronic health records at Santa Elisabeth Hospital Medan: Man. Methods, machines